Nanomaterials for targeted drug delivery for immunotherapy of digestive tract tumors - Li, Mingzhu; Li, Ningxin; Piao, Haozhe; Jin, Shengbo; Wei, Hongzhe; Liu, Qian; Yu, Jun; Wang, Wenping; Ma, Siyao; Jiang, Yuxin; Yao, Huini; Shen, Yue; et al. (Frontiers in Immunology, 2025)
The incidence and mortality rates of digestive tract tumors, especially gastric and colorectal cancers, are high worldwide. Owing to their unique advantages, such as efficient drug loading, safety, and targeting properties, nanoparticles (NPs) have demonstrated great potential in the treatment of gastrointestinal tumors. However, their practical application is limited by several factors, such as high costs, few clinical trials, and long approval periods. In this review, we summarize three types of immunotherapeutic nanomaterial drugs for gastrointestinal tumors: organic, inorganic, and hybrid nanomaterials. This article also discusses the current status of research and development in this field and the advantages of each type of material to provide theoretical references for developing new drugs and advancing clinical research.